Examination of the British Columbia influenza prevention policy for healthcare workers: Phase 1 qualitative case study - Charmaine M. McPherson; Donna M. Halperin; Bonnie Henry; Antonia M. Di Castri; Jeffrey C. Kwong; for the Public Health Agency of Canada/Canadian Institutes of Health Research Influenza Research Network (PCIRN) (Taylor & Francis Group, 2018)
In August 2012, British Columbia became the first Canadian province to implement a province-wide Influenza Prevention Policy requiring all healthcare workers (HCWs) in residential and acute care facilities to either be immunized against influenza, or wear masks in patient care areas during the influenza season. This qualitative case study sought to understand the key facilitators and barriers involved in developing and implementing British Columbia's Influenza Prevention Policy. An explanatory qualitative case study approach was selected for this project. Data were collected through the review of 110 documents (policy and planning documents, implementation tools, press releases, communication materials, etc.), and through 7 focus groups with policy implementation team members (n = 48). Focus group interview transcripts were analyzed using Framework Analysis methods, and Prior's approach guided document analysis. Four themes were identified: (1) Clashing paradigms, (2) Policy implementation gaps, (3) Pathways of power, and (4) Personal impacts. Issues embedded in macro-, meso-, and micro-level contexts, and planning across the province, were identified as critical to policy implementation. A province-wide approach with senior-level engagement and dedicated resources is critical in a province-wide influenza prevention policy for HCW. Recommendations to improve large-scale implementation of condition-of-service influenza policies include: engaging stakeholders early, considering the complexity of political contexts, allotting time to plan appropriately, developing 'enforcement' plans, and providing education and skills to frontline providers.